Development Technology of Military Patriotic Education in the Students of the Call for Military Education (Eurasian Research Bulletin, 2023)
In this article, ideas are put forward about educating young students in the spirit of military patriotism. It is known to everyone that educating young people, who are the future of the state, with high moral qualities, humane, physically strong, patriotic, with military knowledge, in the spirit of national pride is the most urgent issue of today. The article can be used by representatives of relevant fields.